PENGARUH AUDIT TENURE, AUDITOR REPUTATION, DAN UKURAN KOMITE AUDIT TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN (Studi Empiris pada Perusahaan Sektor Property, Real Estate, and Building Construction yang Terdaftar di Bursa Efek Indonesia Periode 2022–2024) - Yohannes Sibarani; Ilham Wahyudi; Misni Erwati (Jurnal Akuntansi Kompetif, 2026)
This study aims to analyze the effect of audit tenure, auditor reputation, and audit committee size on the timeliness of financial reporting in property, real estate, and building construction companies listed on the Indonesia Stock Exchange for the 2022–2024 period. This study employed quantitative methods with secondary data obtained from the companies' annual financial reports. The sampling technique used purposive sampling with a sample size of 15 companies over three years of observation, resulting in 234 observations. The data analysis method used was logistic regression with the assistance of IBM SPSS Statistics 26. The results showed that audit tenure, auditor reputation, and audit committee size simultaneously had no effect on the timeliness of financial reporting. Partially, each variable did not affect the timeliness of financial reporting.